2019
DOI: 10.1186/s40359-019-0366-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients with chronic pain: evaluating depression and their quality of life in a single center study in Greece

Abstract: BackgroundChronic pain constitutes one of the most common reasons for seeking health care services and may even lead to disability. Chronic pain has been associated with depression and deterioration of the quality of life. The aim of our study is to outline the burden of chronic pain in the context of a primary health care (PHC) setting in Greece and to investigate its association with depression and quality of life.MethodsA cross-sectional study was conducted from September 2016 to November 2016. The subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 45 publications
2
29
1
1
Order By: Relevance
“…Following the same analyses, the algorithm learned that subjects with depression (high BDI values) had a higher chance of belonging to the chronic pain group than participants without depression. This feature seems to be supported by previous literature on chronic pain, where several studies have linked chronic pain to depression [ 69 , 70 , 71 , 72 , 73 ]. A similar interpretation could be observed on anxiety (STAI variables), with high values of anxiety being related to chronic pain conditions [ 88 , 89 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Following the same analyses, the algorithm learned that subjects with depression (high BDI values) had a higher chance of belonging to the chronic pain group than participants without depression. This feature seems to be supported by previous literature on chronic pain, where several studies have linked chronic pain to depression [ 69 , 70 , 71 , 72 , 73 ]. A similar interpretation could be observed on anxiety (STAI variables), with high values of anxiety being related to chronic pain conditions [ 88 , 89 ].…”
Section: Discussionsupporting
confidence: 86%
“…The BDI and STAI are two questionnaires associated with depression and anxiety, respectively. These are disorders commonly correlated with chronic pain conditions [ 69 , 70 , 71 , 72 , 73 ]. The QST measures and body location included: pressure thresholds (index finger and wrist), heat threshold (index finger), and cold threshold (index finger, wrist, and elbow).…”
Section: Methodsmentioning
confidence: 99%
“…A high proportion of patients who take antidepressants and opioids concurrently corresponds to the data indicating that depression occurs in 22.5% of patients with chronic pain 30 , while in RA patients depressive symptoms were observed in 12-55% of respondents, depending on the kind of questionnaire used and its level of detail 31 . Moreover, it was determined that in the group of patients with mainly moderate or high RA activity measured with DAS23, a depressive episode in the course of recurrent depression is an important factor in the persistence of pain, and tailored antidepressant treatment leads to a lasting reduction in pain intensity 32 .…”
Section: Opioids and Rheumatoid Arthritissupporting
confidence: 54%
“…Chronic pain interference reflects patients’ perception of the extent to which pain interferes with social relationship, work or daily activities [ 38 ]. Rapti et al’s study also showed that the higher the pain interference, the greater the symptoms of depression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%